Images of Philosophers and Poets and Their Veneration in Late Antiquity - Suslenkov, Vitaly Ye. (Actual Problems of Theory and History of Art, 2023)
The article is devoted to the history of the veneration of philosophers and poets (or sages) in antiquity. One of its forms was the creation of sculptural portraits, mosaics, and fresco paintings, which, according to our opinion, functioned in the environment of some form of a religious cult. Numerous sources (historians, Neoplatonic philosophers, Christian writers) report the attitude toward the sages as prophets, miracle workers, divine intermediaries, and toward their wisdom as a sign of the presence of the deity and, as a result, a way to achieve immortality. This “voice of the epoch” confirms that it is impossible to consider the images of philosophers and poets only as portraits of outstanding representatives of culture, revered in an educated environment — it does not reflect the whole picture. The attitude toward the talent of a philosopher or a poet as inspiration, and toward them as heroes in the ancient sense of the word (and in this sense they are related to mythological heroes, some of whom continued to be depicted in the 4th–6th centuries), could be the main reason why the plot with sages persisted until the 6th century, to a large extent already in the Christian context, and was revived by the 11th century.